Partial amputations of the foot for diabetic gangrene. - Turnbull, A. R. (Royal College of Surgeons of England, 1988)
Over a 5-year period 68 diabetic patients underwent 102 primary partial amputations of the foot for infected diabetic gangrene. Seventy (69%) of these operations healed without further local surgery, but five patients needed seven femoropopliteal bypass grafts (two bilateral) to achieve healing. In total, 32 primary operations needed revision by further surgery to the foot or by leg amputation. Of the original operations 31% were carried out by a consultant surgeon; the rest (69%) were performed by a junior surgeon. By contrast, only four of the 32 operations needing revision (12%) had originally been done by a consultant, whereas 28/32 (88%) had been carried out by a junior surgeon. Of limbs at risk 65/80 (81%) were salvaged. Five patients died during their hospital admission, giving an overall mortality of 7%.